Policies in Village Development: Learning from Community Empowerment and Participation in Jayapura - Fatem, Agustinus (UI Scholars Hub, 2012)
Community empowerment has ample opportunity for accomplishment in the decentralization era and through the implementation of regional and special autonomy in Papua. This research analyzes the influence of community empowerment on community participation in village development in the Jayapura Regency and establishes a model for community empowerment and participation in regional development, using the quantitative approach. Primary data is collected from respondents through questionnaires, interview guides, and on-site observation. Respondents are chosen using the cluster sampling technique (with two or more respondents) to determine sample areas (districts and villages), and respondents from sample villages are chosen using the proportional random sampling technique. Field data is processed and analyzed using the structural path analysis technique and the qualitative-descriptive analysis. According to research findings: (1) participation in village development is influenced by community empowerment, which is shaped by conducive situation, community capacity, and community protection (2) the participatory dimensions in village development are planning, implementation, utilization, and maintenance, and evaluation is partially determined by the significant influence from conducive situation and community capacity. It is our hope that this review on community empowerment and participation in development can contribute to transforming community members into the main agents of development, therefore leading to a development that is “from, by, and for” the community.